Sudden psychotic episode probably due to meningoencephalitis and Chlamydia pneumoniae acute infection - Xavier, Miguel (2017)
Background: Since 9% to 20% of all cases of acute psychosis presenting to an Emergency Department. (ED) are due to a general medieal condition, cautious medical workup should be mandatory in such patients. Differential diagnosis must consider conditions as diverse as renal failure or CNS infection. Acute Chlamydia pneumoniae infection usually causes a self-limited respiratory syndrome. Rarely, acute neurological complications occur, with acute meningoencephalitis most frequently reported. Diagnosis requires a high level of suspicion and is difficult to confirm. Case report: We describe a 22 year-old female Caucasian who, three days after a mild pharingitis, developed an acute psychosis with exuberant symptoms interspersed with periods of lucidity, in a background of normal consciousness and orientation. Initial medical and imagiological workup were inconclusive. After 20 days of unsuccessful treatment with antipsychotics she developed a high fever and was re-evaluated medically. Lumbar puncture revealed an inflammatory cerebrospinal fluid. MRI showed irregular thickening and nodularity of the lateral ventricles' lining. An anti-Chlamydia pneumoniae IgM antibody titter of 85 IU/ml was detected. All symptoms cleared after treatment with antibiotics and corticosteroids. Conclusion: This is, to our knowledge, the first reported case of acute CP-associated meningoencephalitis manifesting as an acute psychotic episode. It illustrates the principle that non-organic psychiatric syndromes must remain a diagnosis of exclusion in first-time acute psychosis.